Chain: the relationships that break us, the women who rebuild us - Suleyman, Chimene (London Weidenfeld & Nicolson, 2024)
In January 2017, Chimene Suleyman was on her way to an abortion clinic in Queens, New York with her boyfriend, the father of her nascent child. It was the last day they would spend together. In an extraordinary sequence of events, Chimene was to discover the truth of her boyfriend's life: that she and many other women had been subtly, patiently and painfully betrayed. In this spellbinding memoir, she exposes one man's control over many women and the trauma he left behind, and celebrates the sisterhood that formed in his wake despite - and in spite of - him. Exploring how women are duped every day by individuals, she interrogates how society itself continually allows this to happen. She demonstrates that, no matter how intelligent, educated or self-aware they might be, over time a woman can be played into performing the age-old role of giver and nurturer: self-sacrificing and subordinate. Both a devastating personal testimony and a searing indictment of persistent misogyny, The Chain is a book for any woman who has questioned her relationship and buried her doubts, for any woman who can't quite identify the source of her unease and for any woman who has been sheltered by the fierce protection of her female friends.
Keywords: English Tale; Non Fiction